VARIASI TEMPERATUR PEMANASAN MULA PADA SIFAT MEKANIK PENGELASAN BAJA SS400 - Rusnoto, Rusnoto; Prasetyo N, Agung; S, Irfan; RW, Galuh (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2022)
This study aims to determine the mechanical properties, namely bending and hardness of the SS400 steel welding results which previously carried out variations in the preheating temperature on the SS400 steel plate. The materials and tools used are SS400 AWS e7018 Electrode Steel, a welding machine. The specimen is initially in the form of a plate sheet which is then shaped into a test specimen. After the specimen is finished, it is then heat treated using a heating furnace with temperatures of 90, 100, and 1100 C with a holding time of 30 minutes.From the data from the test results of this study, namely the testing of hardness and bending, it shows that there is an influence from the preheating process on welding S$400 steel plate, namely the increase in the highest hardness value at 1100 C of 8.41 HB, and bending strength at preheating temperature of 1100 C of 18.62 N/mm2, compared to those without preheating before welding.Keywords: preheating, SS400 steel, temperature, hardness, bending